Solid-solution strengthening in refractory high entropy alloys. (15th August 2019) - Coury, Francisco Gil; Kaufman, Michael; Clarke, Amy J.
Abstract: Compression stress-strain curves of a number of refractory high entropy alloys (RHEAs) were generated at temperatures ranging from room temperature to 1000 °C. It is shown that solid-solution strengthening in these alloys has both an athermal and a thermal component. Results from mechanical testing are combined with literature data to develop solid-solution strengthening models for both components that incorporate the particularities of single-phase body centered cubic (BCC) materials. The athermal component is affected by a combination of atomic size mismatch and elastic modulus mismatch, which depend upon average values from each alloy, thereby allowing this component to be estimated in a high-throughput fashion. On the other hand, the thermally-activated yield stress component does not correlate with any parameter that can be calculated by averaging pure elemental atomic properties and it is observed to be larger than the values found for pure BCC refractory metals and their dilute alloys. Overall, RHEAs are found to have larger thermal and athermal yield stress components compared to pure or conventional refractory alloys, which explains their relatively high strengths at room temperature. Graphical abstract: Image 1